PENGARUH TEKNIK HERRINGBONE TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAN SISWA KELAS XI BAHASA SMAN 1 TAMAN - Taufik, Mochammad Rizal; Wahyuningsih, Fahmi (LATERNE, 2023)
Reading comprehension is an ability that must be mastered by students in language subjects, one of which is German. By mastering this ability, students can study the text well so that it will indirectly improve their learning outcomes. The purpose of this study was to determine (1) the effect of the herringbone technique on the learning outcomes of reading comprehension; (2) the effect of direct learning techniques on learning outcomes of reading comprehension; and (3) the difference in the effect of the herringbone technique and direct learning techniques on learning outcomes to understand the students' understanding of class XI language at SMAN 1 Taman. This study used an experimental method using control and experimental classes as well as pretest and posttest testing. The treatment in the experimental class was applying the herringbone technique and in the control class using direct learning. The experimental class in this study is class XI Odd Languages and the control class is XI Even Languages. This this time that (1) the results of learning to read comprehension using the herringbone method in the experimental class showed significant results with a significance value of 0.000 and an average increase of 15.4%; (2) the results of learning to read comprehension with the direct learning method in the control class showed significant results with a significance value of 0.000 and an average increase of 6.25%; and (3) the difference in the results of learning to read comprehension with the herringbone method and direct learning in the experimental and control classes showed a significant difference with a significance value of 0.007 and an average difference of 6.85% which was superior to the experimental class.